KESEPAKATAN INGGRIS TERHADAP EUROPEAN UNION-UNITED KINGDOM TRADE AND COOPERATION AGREEMENT (TCA) PASCA BRITAIN EXIT 2020 - Nabila Arista Wedhea; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The results of the Brexit referendum in 2016 with a majority of people voting to leave the European Union made the UK no longer bound by all rules originating from the European Union. During the Brexit transition period, the UK designed and prepared a new government and negotiated a future cooperative relationship with the European Union. Through 9 rounds of cooperation negotiations with the European Union, on 24 December 2020 British and European Union negotiators reached an agreement on a cooperation agreement. The EU-UK Trade and Cooperation Agreement has changed the basics of Britain's relationship with the European Union to become a free trade and cooperation relationship. This paper shows the factors used by the UK to determine its foreign policy in agreeing to the TCA. This research uses the perspective of neo-liberalism and foreign policy theory. The method used in this research is explanatory qualitative with literature study data collection techniques both physical and digital. The results showed that the UK's decision to agree on the TCA was due to internal and external factors that influenced the UK's decision. Britain's internal factors can be seen in the implications of Brexit on the British economy, interest in regulating access to and operating transportation services, and interest in managing aquatic resources. Indicators of the UK's external factors are the ease of access to EU countries, the threat of terrorism from outside, eliminating the European Union's tariff barrier, and increasing foreign investment from the EU. Keywords: EU-UK Trade and Cooperation Agreement, Brexit, European Union